2009
DOI: 10.3382/japr.2008-00014
|View full text |Cite
|
Sign up to set email alerts
|

Performance and profitability of second-cycle laying hens as influenced by body weight and body weight reduction during molt

Abstract: An experiment was conducted to determine the effects of hen BW before molt and the percentage of BW loss during molt on the subsequent performance and profitability of hens during the second cycle of production. Results revealed that profits associated with Light hens (≤1,453 g, or 3.2 lb) were from 1.8¢ to 3.8¢/dozen eggs higher than those associated with Heavy hens (≥1,589 g, or 3.5 lb). Profits of Nonselected hens (ranging from 1,090 to 2,134 g, or 2.4 to 4.7 lb) were intermediate, ranging from 1.2¢ to 2.5¢… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
3
4
0
1
Order By: Relevance
“…In agreement with the observations of Gordon et al (2009), it became evident from the present results that profits associated with lighter hens like ISA Brown and Sonali were higher than those associated with heavy profitability of lighter hens was hens such as RIR and Cobb 500 and the increased largely due to their improved feed conversion, because lighter hens produced predominantly larger or extra large eggs. Broiler farming with Cobb 500 was reported profitable because of lower investment, less space requirement, utilization of family labour and quick returns as examined by Islam et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…In agreement with the observations of Gordon et al (2009), it became evident from the present results that profits associated with lighter hens like ISA Brown and Sonali were higher than those associated with heavy profitability of lighter hens was hens such as RIR and Cobb 500 and the increased largely due to their improved feed conversion, because lighter hens produced predominantly larger or extra large eggs. Broiler farming with Cobb 500 was reported profitable because of lower investment, less space requirement, utilization of family labour and quick returns as examined by Islam et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…Showing an increase of egg mass during the first cycle of molting from the regular production cycle expressed in index points clearly indicates the trend of their increase and shift their weight to heavier classes. The same results were obtained in the research conducted by Gordon et al, 2009. By organizing data obtained from regular production cycle and the first molting process there was noticed very significant differences in the parameters that are logically impose such a conclusion.…”
Section: Day Of Exploitationsupporting
confidence: 77%
“…During the transition phase of the birds from the chicks to the growers (i.e., between week 10 and 12), there was a period of physical adjustment to the new feeds between week 10 and 12. Leeson and Summers [79] and Mwaniki et al [21] revealed that birds are usually physically challenged before the onset of egg laying with great potential for negative nutrient balances to occur. This explains why young birds must be provided with adequate energy and nutrient-rich feeds for proper body build up before the onset of egg laying.…”
Section: Discussionmentioning
confidence: 99%